The Influence of Transformational Leadership Style, Work Environment, and Work Motivation on Employee Performance: Pengaruh Gaya Kepemimpinan Transformasional, Lingkungan Kerja, dan Motivasi Kerja Terhadap Kinerja Karyawan - Husain, Fachri Ramizard; Sumartik, Sumartik (Indonesian Journal of Law and Economics Review, 2023)
This study aims to explain and determine the effect of leadership style, compensation, and work environment on the performance of employees UD. Fathona Bakey Kec-Gempol. This research is a type of quantitative research with hypothesis testing. The sample used in this study is the entire population of 55 employees of UD.Fathona Bakery. The analytical tool used in this study is multiple linear regression analysis using SPSS version 22 for windows. The primary data in this study were obtained from questionnaires and company archives whose measurements used a Likert scale which were tested for validity and reliability.The results of this study prove that leadership style partially has a positive effect on employee performance. Compensation partially has a positive effect on employee performance. The work environment partially has a positive effect on employee performance. Transformational leadership style, work environment, and work motivation simultaneously have a positive and significant effect on employee performance.